African American parental values and perceptions toward children's playfulness - Porter, Carolyn A., author; Bundy, Anita C., advisor (Colorado State University. Libraries, 1997)
Since play is the primary occupation of children, and parents have a significant influence in children's lives, it is important to understand the values, beliefs, and childrearing goals of parents in a multicultural society. This study explored the relationship between African American parents' values and beliefs about playfulness and their children's observed playfulness. Forty-seven African American parents from a middle socioeconomic background and their children participated in this study. Observational assessments, the Test of Playfulness (ToP; Bundy, 1997) and the Children's Playfulness Scale (CPS; Barnett, 1990) were used to measure a child's playful approach. Parents completed questionnaires about their children's playfulness (CPS), and their children were observed during free play (ToP). The findings revealed that African American parents shared similar values about playfulness to parents from other cultures. African American parents valued the social and joyful aspects of playfulness highly, whereas items reflecting humor were valued the least. Also, the CPS and ToP are both valid measures of playfulness with African American parents and their children. The results suggested that mothers may be more accurate in judging children's playfulness than fathers. Cultural influences, parental experience, and parents' developmental goals may be contributing factors. Discussion on the significance of the results, recommendations for future research, and a review of African American theoretical conceptions, family characteristics, parental beliefs, and the relationship of play and culture are highlighted.
Keywords: Play assessment (Child psychology); Play -- Cross-cultural studies; African American parents